The Late Antique Imperial Palace in Polače on the Island of Mljet - Peković, Željko (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
In his analysis of imposing remains of the late antique palace in Polače on the island of Mljet, the author revises observations of other researchers, as well as their proposed reconstruction of the palace, its plan and elevation. For the first time, traces of the palace structural system are discussed in detail, and functions of rooms on the ground and upper floor are proposed. The palace on Mljet is contextualized in terms of the late antique residential architecture on the eastern Adriatic coast, which resulted in the detection of many points of contact with the residential tract of Diocletian’s Palace in Split.